Agronomic response of three varieties of brachiaria in canton El Empalme Guayas province, Ecuador - Luna Murillo, Ricardo (2016)
In this paper, the agronomic response of three varieties of Brachiaria (B. decumbens; B. brizantha and B. hybrid cultivar cv. Mulato (CIAT 36061) was evaluated, as a contribution to improving animal production in Ecuador. A randomized block design in factorial arrangement (2x3) with three replications was conducted, with a total of 54 plots. Two localities and three stages of maturity (21; 42; 21 and 63) were evaluated. The variables evaluated were plant height, number of leaves and stems, leaf:stem and forage biomass. The varieties studied had superior performance in the town’s Guayas, in relation to the characteristic acidic of soil in the area. B. mulatto grass was superior in producing foliage to other varieties. At 63 days, the highest values were observed in plant height (98.57 cm), number of leaves (774.84) and stems (162.51). The weight of leaf (6.48 t MS/ha-1) yield was higher at 42 days. Biomass production showed a yield increase with increasing age of regrowth. It is concluded that in the town’s Guayas Brachiaria species studied had superior performance, excelling B. mulatto, mainly in performance. The age cutoff had a marked effect on the behavior of the indicators evaluated to increase performance.